Pengembangan Media Pembelajaran E-Flashcard Untuk Meningkatkan Keterampilan Membaca Permulaan Peserta Didik Kelas 1 Sekolah Dasar - Nadila Resti Cahyanti; Nanda William; Wahyu Nurmalasari (Jurnal Elementaria Edukasia, 2023)
The purpose of this research is to develop an E-Flashcard learning media to improve early reading skills. The focus of the study is to determine the early reading skills of first-grade students at SDN 1 Tamanan and SD Islam Al Badar, describe the design, validity, and explain the effectiveness of the E-Flashcard learning media in improving the early reading skills of first-grade students. The research method used is research and development (R&D) with the ADDIE development model. The data collection techniques used in this study are observation, interviews, media validation, content validation, practitioner validation, student response questionnaires, teacher response questionnaires, as well as pre-test and post-test instruments for oral early reading skills. Based on the t-test, a sig. (2-tailed) value of 0.00 was obtained for the pre-test and post-test. Meanwhile, the effectiveness test results (n-gain) obtained a mean n-gain value of 75.68, which is > 75. Therefore, it can be concluded that the use of E-Flashcard learning media is highly effective in improving the early reading skills of first-grade students in elementary schools.